Enzymatic Production of Fatty Acid Methyl Esters by Hydrolysis of Acid Oil Followed by Esterification - Watanabe, Yomi; Nagao, Toshihiro; Nishida, Yutaka; Takagi, Yoshiaki; Shimada, Yuji (Journal of the American Oil Chemists' Society, 2007)
Abstract Acid oil, a by‐product of vegetable oil refining, was enzymatically converted to fatty acid methyl esters (FAME). Acid oil contained free fatty acids (FFA), acylglycerols, and lipophilic compounds. First, acylglycerols (11 wt%) were hydrolyzed at 30 °C by 20 units Candida rugosa lipase/g‐mixture with 40 wt% water. The resulting oil layer containing 92 wt% FFA was used for the next reaction, methyl esterification of FFA to FAME by immobilized Candida antarctica lipase. A mixture of 66 wt% oil layer and 34 wt% methanol (5 mol for FFA) were shaken at 30 °C with 1.0 wt% lipase. The degree of esterification reached 96% after 24 h. The resulting reaction mixture was then dehydrated and subjected to the second esterification that was conducted with 2.2 wt% methanol (5 mol for residual FFA) and 1.0 wt% immobilized lipase. The degree of esterification of residual FFA reached 44%. The degree increased successfully to 72% (total degree of esterification 99%) by conducting the reaction in the presence of 10 wt% glycerol, because water in the oil layer was attracted to the glycerol layer. Over 98% of total esterification was maintained, even though the first and the second esterification reactions were repeated every 24 h for 40 days. The enzymatic process comprising hydrolysis and methyl esterification produced an oil containing 91 wt% FAME, 1 wt% FFA, 1 wt% acylglycerols, and 7 wt% lipophilic compounds.